E-healthcare for diabetes mellitus type 2 patients - a randomised controlled trial in Slovenia - Iljaž Rade; Brodnik Andrej; Zrimec Tatjana; Cukjati Iztok (Sciendo, 2017)
Telemonitoring and web-based interventions are increasingly used in primary-care practices in many countries for more effective management of patients with diabetes mellitus (DM). A new approach in treating patients with diabetes mellitus in family practices, based on ICT use and nurse practitioners, has been introduced and evaluated in this study.